WOMEN PARTICIPATION IN TEACHING AND RESEARCH IN HUMAN ANATOMY - FACULTY OF MEDICINE, NOVI SAD, SERBIA - Mirela Eric (Asociación Argentina de Anatomía Clínica, 2023)
At the Faculty of Medicine in Novi Sad, women comprise the majority of enrolled medical students, and over the last decade representation is about 70%. Out of the total number, more than 3/4 of teachers are women at the Departmen of Anatomy in Novi Sad. All teachers (women and men) are Doctors of Medicine and moreover, two professors are specialists in surgery and psychiatry, while one professor and two teaching assistants are residents. Situation of our Department regarding the representation of female teachers is above the national average (76.92% vs. 55.74%).